Rutabaga—Brassica napus L. (Napobrassica group) - James M. Stephens (EDIS)
This document provides an overview of rutabaga (Brassica napus L., Napobrassica group), a cool-season root vegetable related to turnips and cabbage. It describes the plant’s distinguishing features, including bluish-green leaves and yellowish flesh, and outlines its cultivation requirements in Florida, emphasizing its tolerance to frost and long growing season. The document also lists common varieties and details its culinary uses, such as baking, mashing, and inclusion in soups and salads. Original publication date May 1994.